y-5.6=-3.5

Simple and best practice solution for y-5.6=-3.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-5.6=-3.5 equation:



y-5.6=-3.5
We move all terms to the left:
y-5.6-(-3.5)=0
We add all the numbers together, and all the variables
y-2.1=0
We move all terms containing y to the left, all other terms to the right
y=2.1

See similar equations:

| (2x+1)^2-6=0 | | 47(2x)=94 | | -28=f/7-34 | | (2x+1)^2=6 | | 5(2x+1)^2-30=0 | | 9(2m-3)^2+8=449 | | 8-4d=20 | | 4x-12=2x+15 | | 5(2x+1)^2=30 | | 1x−15=4x−3 | | 12=j/4+9 | | -3(w+2)=2(w+6+7 | | n,n+7=8+n | | 34=6(x+3)-8x | | 3y²-11y+10=0 | | 3x-10=4x-45 | | 60000(3x-1)=120,000 | | y²=0-9 | | 3+p2=7 | | (6x+2)^2+4=28 | | 5=3q-13 | | 06.x-5=0.1x+7 | | t(49)=7(49) | | (5x-14)=(2x+7) | | 28-5m=2 | | t(49)=7(49 | | 7=p/3+6 | | 8x^2-16x+140=0 | | -1=4/3w-1/3w | | 4x-12=15+12 | | 3(x+2)=7x−6 | | 16+3x-8=20 |

Equations solver categories